2019
DOI: 10.1259/bjr.20180833
|View full text |Cite
|
Sign up to set email alerts
|

Should we be moving to a national standardized non-gadolinium MR imaging protocol for the surveillance of vestibular schwannomas?

Abstract: Getting It Right First Time (GIRFT) is a UK national programme designed to improve the quality of care within the NHS by reducing unwarranted variations. By tackling variations in the way services are delivered across the NHS, and by sharing best practice between trusts, GIRFT identifies changes that will help improve care and patient outcomes, as well as delivering efficiencies such as the reduction of unnecessary procedures and cost savings. 1 Imaging performed for the surveillance of patients with non-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Studies also shown noncontrast T2WI to be accurate in the detection of interval growth in patients with known, surgically-naïve vestibular schwannoma. 17,18 To our knowledge, no studies exist examining the use of noncontrast T2WI for postoperative surveillance.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Studies also shown noncontrast T2WI to be accurate in the detection of interval growth in patients with known, surgically-naïve vestibular schwannoma. 17,18 To our knowledge, no studies exist examining the use of noncontrast T2WI for postoperative surveillance.…”
Section: Abbreviationsmentioning
confidence: 99%
“…2 These steady-state imaging sequences currently include various manufacturer-specific sequences such as CISS (Constructive Interference into Steady State, Siemens), FIESTA-C (Fast Imaging Employing Steady-state Acquisition Cycled Phases, GE), DRIVE (Driven Equilibrium Radiofrequency Reset Pulse, Philips), bFFE (Balanced Fast Field Echo, Philips) and SPACE (Sampling Perfection with Application optimized Contrasts using different flip angle Evolutions, Siemens). 3 The submillimeter-resolution images from these sequences can be manipulated on computer-based DICOM imaging software to provide reformatted images in non-orthogonal planes that allow visualization of the entire 8 th cranial nerve, from the brainstem to the fundus of the internal auditory canal. In these sequences, cerebrospinal fluid (CSF) displays a high signal intensity that provides an excellent contrasting background to the inherent low signal intensity of the 7 th and 8 th cranial nerves.…”
mentioning
confidence: 99%